Comparison of expulsion and complications of intrauterine device insertion in immediate post placental period with interval period: a prospective study - Jamkhandi, Supriya S.; Tile, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In India unmet need for contraception is estimated to be 15.8% as estimated by DHS survey. Immediate insertion of IUCD after delivery of placenta provides important opportunity to address the need for contraception. This study was carried out to evaluate complications and expulsion rates of immediate post placental insertion of IUCD in comparison to interval insertion. Methods: This was a prospective clinical study conducted at ESIC medical college and district hospital, Kalaburgi, Karnataka, India with sample size of 150 women (50 each in vaginal, cesarean delivery and interval insertion) from June 2015 to Jan 2016. Results: Majority of women were multipara with mean age of 27.5 years. There was no statistically significant difference in the overall rates of complication in each group in follow up period (p= 0.7, 0.9, 0.5 for bleeding, pain and infection respectively).While comparing expulsion rates among the three groups, vaginal delivery (group A) had higher expulsion 6%, trans cesarean insertion (group B) had one expulsion 2% and there were no expulsion in interval insertion (group C). The difference was found to be statistically significant among group A and C. Conclusions: From above study postpartum insertion of IUCD is safe, effective and feasible reversible method of contraception. The rate of expulsion is higher in postpartum insertion compared to trans cesarean and interval insertion, can be minimized if it is inserted by trained provider and placed at fundus. The continuation rates were comparable in three groups i.e., 94%, 96% and 100% respectively.